Immune-Related Multiple-Organs Injuries Following ICI Treatment With Tislelizumab in an Advanced Non-Small Cell Lung Cancer Patient: A Case Report - Deng, Chao; Yang, Meng; Jiang, Hong; Wang, Renbin; Yang, Zhaojun; Sun, Hongliang; Cui, Huijuan (Frontiers in Oncology, 2021)
Immune-related adverse events (irAEs) following treatment with immune checkpoint inhibitors (ICIs) can affect almost any organ systems. Multiple-organs irAEs are a rare occurrence which makes its management and treatment very challenging. This is a case report of a 71-year old man with advanced non-small cell lung cancer (NSCLC) who developed multiple-organs irAEs (lung, muscle, myocardium, liver, and pituitary) after a single cycle (21 days) of the BGB-A317 (Tislelizumab). After more than two months of immunosuppression treatment with glucocorticoids, the tumor and inflammatory lesions in the lung were reduced. The levels of serum creatase, cardiac troponin T (TNT), and hepatic transaminase were also reduced. Four months after the termination of ICI therapy, the lung tumor reappeared in the previous site. This rare case report supplies several experiences in the management of multiple-organs irAEs, including full-scale monitoring of immunological indicators, early differential diagnosis, and prompt glucocorticoid therapy. This patient was not a candidate for the ICI re-challenge therapy due to the number and seriousness of irAEs. Multiple-organs irAEs add complexity to the management, and additional research is needed to develop optimal therapeutic guidelines.